Adiponutrin (PNPLA3) in liver fibrogenesis: Is unaltered HepG2 cell line a better model system compared to murine models?. Issue 6 (December 2015) - Dutta, Atanu Kumar
Abstract: Alcoholic liver disease is a major source of morbidity and mortality worldwide. Twin studies had demonstrated heritability of alcoholic liver disease. Although to date only Adiponutrin (PNPLA3) rs738409 polymorphism (I148M) had been unequivocally proved to be associated with increased risk of alcoholic liver disease across different ethnicities. This protein was previously thought to have a predominant lipolytic role. However, recent investigations have provided evidence of lipogenic activity of this protein. The current hypothesis paper is summarizing the recent evidences gleaned in biological role of Adiponutrin and bioinformatic pointers towards a role in lipid trafficking. A critical appraisal of the utility of murine models and cell based systems in investigating Adiponutrin is also presented. As the HepG2 cell line harbors the I148M mutation in homozygous state it is hypothesized that this should represent an ideal model system for PNPLA3 biology. Thus, as Adiponutrin is proposed as having both lipolytic and lipogenic/lipid trafficking roles it is termed as a Yin–Yang protein in analogy to ancient Chinese wisdom.